Strategi Pengembangan Produk di Industri Media Cetak di Indonesia : Bertahan di Tengah Persaingan dengan Media Online - Asep Saefurahman; Nina Allyssa (Master Manajemen, 2025)
Understanding the printing press industry position in the product life cycle is very important. This is to determine the right strategy for the printing press in order to be exist and profitable. When we see the condition of the printing press which is facing tough competition with internet-based media beside the uncertain challenge ahead, the printing press industry is in the maturity phase. In this position is required precise product development strategy. The strategy can be done by creating new products with expands in a press online and by improving the quality, either by changes in product design or improvement of product quality print journalism.